Palliative care through single visit flexible feeding aid for an infant with Pierre Robin sequence: A clinical report - Manu Rathee; Mohaneesh Bhoria; Madhuri Dua (Wolters Kluwer Medknow Publications, 2015)
Pierre Robin sequence (PRS) or anomalad is one of the most readily recognized presentation, and results of the first brachial arch malformation. PRS presents a classic triad of micrognathia, glossoptosis, and cleft palate. Infants with PRS can present with varied problems, some of them emergencies. However, in infants with a complete cleft palate, most commonly encountered problems are with feeding. This article describes the clinical and laboratory procedures for construction of a feeding plate in a neonate with PRS due to the presence of a cleft palate.